A linguagem pensada a partir das filosofias de Nietzsche e de Wittgenstein - Ferreira, José Carlos Souza (2020)
Abstract: The specific objectives of this dissertation are two: to understand the peculiarities of the Nietzsche’s philosophy of language and of the so-called “second” Wittgenstein’s philosophy of language and to develop, from this, a comparative approach between both. For this purpose, we will divide the theme of language thought out from the philosophies of Nietzsche and of Wittgenstein as follows: in the subchapter 1.1, We will examine the way in which Nietzsche conceives language in the booklet On truth and lie an extra-moral sense; in the 1.2, we will analyze the unfolding of the extra-moral approach of the language in Nietzsche’s mature philosophy, especially in The Genealogy of Morals; after, in the subchapter 2.1, we will approach the logical-metaphysical deadlocks that Wittgenstein encountered in the Tractatus logico-philosophicus , forcing him to radically review his language conception; in the 2.2, we will analyze the way in which the language is thought by Wittgenstein in the second phase of his route philosophical, mainly in Philosophical investigations; posteriorly, in the subchapter 3.1, the importance of language in the philosophies of Nietzsche and of Wittgenstein will be examined; in the 3.2, we will approach some possible approximations between the thoughts of Nietzsche and Wittgenstein, regarding to the theme of language; finally, in subchapter 3.3, we will list some divergences between these thoughts, in concerning to the nature and to the purpose of the philosophical approach of language.